Quantitative manoeuvring characteristics of an underwater vehicle equipped with collective and cyclic pitch propeller - Hung Nguyen; Dubois, A; Zhi Quan Leong; Jonathan Binns; Minh Tran (2018)
Operating an underwater vehicle at low speed, such as docking (homing), stationary keeping and under-ice navigation, in severe and harsh environments is a great challenge. Applications of underwater vehicles have been widened from small underwater/subsea missions to complicated under-ice missions such as in the Arctic and Antarctic areas. To fulfil the complicated missions in such harsh environmental conditions, the conventional propulsion systems for underwater vehicles are not appropriate any more, thus operation of such underwater vehicles requires new types of propulsion system to enhance efficiency, to prolong operating time period and to effectively operate underwater vehicles at very low speed. A novel type of propulsion system, namely controllable and cyclic pitch propeller (CCPP), has been designed for underwater vehicles and its performance has been quantified by Computational Fluids Dynamics (CFD) simulation and towing tank captive tests. The idea of a CCPP for an underwater vehicle comes from the rotor of a helicopter. The current investigation shows a great potential of this type of propulsion system to be an alternative propulsion system in order to improve omni-directional manoeuvring characteristics and controllability. This paper is to report on the latest information on quantification of the performance of the underwater vehicle equipped with the CCPP using numerical and experimental approaches.